Pengembangan Instrumen Tes IPA pada Kompetisi Sains Madrasah Se-Kecamatan Bantur Malang - Andi Wibowo (IBTIDA', 2020)
This study aims to develop a valid and reliable natural science test instrument. This test instrument was used to measure the ability of students in the Kompetisi Sains Madrasah (KSM) Bantur District, Malang Regency. This study is a research and development that adapts Borg & Gall's R&D model. The study subjects were 60 elementary school students in the field trial and instrument implementation on 14 students participating in KSM. Research procedures include (1) preliminary studies, (2) planning, (3) initial product development, (4) first revision, (5) field trials, (6) second revision, (7) implementation of test instruments, and (8) ) dissemination. Data collection techniques used interviews, questionnaires, and written tests. The instruments used were interview guide sheets, product validation questionnaire sheets, and question sheets. The data analysis techniques included first, product validity analysis, the second analysis of the empirical validity and reliability of the instrument was carried out with the help of the Rasch Ministep (Winsteps) software. The results of the study were 25 multiple choice questions for the science test instrument. The product developed is valid and reliable with a very good rating (A). Based on the results of field trials, it shows that the 25 questions developed are empirically valid. The reliability results also show a good category with the item reliability 0.90. The results of the implementation of the science test instrument showed that the student's highest score was 72, while the lowest score was 40.